Cytotoxic T cells against herpes simplex virus in Behçet's disease. - Hamzaoui, K (1990)
Lymphocytes from 36 patients with Behçet's disease (20 in remission and 16 in active phase) were stimulated in vitro with herpes simplex virus and then tested for their ability to generate cytotoxic T cell responses to the virus. Significant cytotoxic responses were found. CD4+ and CD8+ subpopulations from the patients in remission generated specific cytotoxic activity against autologous target cells. These observations suggested that CD4+ and CD8+ cytotoxic T cells may have an important host response in herpes virus infection in Behçet's disease.